Changes in patient conceptualization of asthma and asthma self‐management at key timepoints across the COVID ‐19 pandemic: A qualitative study - Aphra Kite; Daniela Ghio; Chris Keyworth; Tracy Epton (British Journal of Health Psychology, 2026)
Abstract Background The COVID‐19 public health emergency had significant impacts on people living with long‐term health conditions. The specific impacts of COVID‐19 on people with asthma across key stages of the pandemic are less certain. This study therefore aimed to explore the experiences of people with asthma across the pandemic as risk levels changed in a retrospective cross‐sectional study. Methods Semi‐structured interviews ( N = 20), conducted at one timepoint, asked about experiences covering pre‐COVID, initial outbreak/lockdown, restrictions lifting, key‐stages salient to them (e.g., vaccination) and longer‐term. Data were analysed using thematic‐analysis. Findings There were three themes. ‘ Doing my own risk assessment ’ was an active process using pre‐existing/acquired knowledge to determine risk and subsequent asthma‐management/COVID‐19 behaviours at all stages. ‘ Asthma from background to foreground ’ highlighted how asthma that was mostly previously unobtrusive was suddenly a ‘pre‐existing condition’ leading to prolonged stress and anxiety. ‘ Place in society ’ describes how the participants were included/excluded by society due to safety concerns from the initial outbreak onwards, which was influenced by government, friends, family and neighbours, the media, health care systems and even themselves. Discussion Findings highlight how some people with asthma experienced the pandemic as a threat to mortality, with evidence of both poor and good adjustment to their asthma management, as per the Transdiagnostic model. When there are future rapid changes in contexts affecting long term conditions, government agencies should use the present study's findings to (a) guide decision‐making, (b) inform public health messaging aimed at targeting at‐risk populations and (c) provide support for at‐risk populations.